2016
DOI: 10.2485/jhtb.25.157
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Angiogenesis in Bone Defect Healing Process due to the Difference in the Frequency of Low-Intensity Pulsed Ultrasound (LIPUS)

Abstract: Low-intensity pulsed ultrasound (LIPUS) is known to promote bone defect healing and also angiogenesis. It was reported the frequency of the LIPUS was related to directivity and the depth of penetration, but the differences in angiogenesis during bone defected healing remains unknown. The aim of this study is to investigate the effect of low and high frequency LIPUS exposure for the angiogenesis during rat femur bone defect healing process by molecular biological and histomorphological evaluations. Bone defects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Sasaki et al (15) reported accelerated capillary vessel formation in LIPUS-stimulated bone. Based on our results, we hypothesize that LIPUS induces angiogenesis that affects bone metabolism in defect areas of the tibia.…”
Section: Discussionmentioning
confidence: 99%
“…Sasaki et al (15) reported accelerated capillary vessel formation in LIPUS-stimulated bone. Based on our results, we hypothesize that LIPUS induces angiogenesis that affects bone metabolism in defect areas of the tibia.…”
Section: Discussionmentioning
confidence: 99%
“…LIPUS is a type of mechanical energy that is transmitted through and into biologic tissues as an acoustic pressure wave at frequencies above the limit of human fracture healing. LIPUS is used widely in medicine as a therapeutic, operative, and diagnostic tool and promotes healing of fractures and bone defects . In this study, the effects of different frequencies of LIPUS for bone formation on scaffolds were investigated by molecular biologic and histomorphologic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Takebe et al reported increased new bone growth in the low‐frequency (1‐MHz) LIPUS group compared with the control group and high‐frequency (3‐MHz) LIPUS group in rabbit sinus augmentation models. Sasaki et al concluded that 1.5 MHz of LIPUS exposure more effectively promoted vascular endothelial growth factor expression and angiogenesis compared with 3 MHz for rat femur bone defect healing. On the other hand, Monden et al reported no significant differences in the gene expression of bone differentiation markers and the volume of newly formed bone in the rat femur bone defective area between the 1.5‐ MHz and 3‐ MHz groups.…”
Section: Discussionmentioning
confidence: 99%
“…LIPUS exposure is known to accelerate not only osteoblastic cell maturation and bone fracture healing but also angiogenesis (Chen et al., ). Angiogenesis plays a role in early bone repair and ossification by creating new blood vessels, which bring oxygen, inflammatory cells and bone precursor cells to the injury site (El‐Bialy et al., ; Hankenson, Dishowitz, Gray, & Schenker, ; Sasaki, Monden, Yoshinari, & Yajima, ). We suggest that the most effective time point for LIPUS application corresponds to the angiogenesis stage, and a constant but non‐significant increase was shown from 18 to 20 weeks (Figure ad,bd and cd).…”
Section: Discussionmentioning
confidence: 99%